Digital motivation for cervical cancer screening: A quasi-experimental trial of the SeDAR Video among middle adulthood Malaysian women - Rodziah Romli; Azmawati Mohammed Nawi; Rahana Abd Rahman; Emma Mirza Wati Mohamad; Kah Teik Chew; Syahnaz Mohd Hashim (PLoS ONE, 2026)
Background Cervical cancer screening (CCS) is a well-established method for preventing cervical cancer (CC). Electronic health (e-health) interventions have shown potential in disseminating health education and are widely used in developed countries to enhance preventive efforts against CC. This study aimed to evaluate the effectiveness of the electronic health video SeDAR® in increasing CCS uptake, knowledge, and motivational factors related to screening. Methods The SeDAR® e-health video was designed based on the Protection Motivation Theory (PMT), incorporating elements such as perceived vulnerability, perceived severity, threat appraisal (fear), coping appraisal, response efficacy, perceived self-efficacy, and protection motivation. It was validated by health experts, media professionals, and female users. A quasi-experimental study was conducted among 76 women, with 38 participants each in the intervention and control groups. The control group received digital pamphlet as intervention tool. Logistic regression was used to assess the impact of SeDAR® on CCS uptake, while repeated measures ANCOVA examined changes in knowledge and motivational constructs. Results The attrition rate of participants is 13.2% with the final sample sizes of 35 (7.9%) and 36 (5.3%) in the SeDAR® and control group, respectively. Participants in the SeDAR® intervention group were significantly more likely to undergo CCS (adjusted odds ratio: 7.26, 95% CI: 1.71–30.74, p = 0.007). While no significant difference was observed in knowledge levels between groups, three motivational constructs showed significant changes. Increases in perceived self-efficacy and protection motivation, along with a reduction in threat appraisal (fear), were associated with greater CCS uptake. Conclusion The SeDAR® e-health video demonstrates effectiveness as a health promotion tool for enhancing motivation and uptake of cervical cancer screening. It offers a promising, scalable approach to support preventive health behavior among women. The authors confirm that all related trials for this intervention are registered under ClinicalTrials.gov with protocol registration number NCT05426642 and release date on June 20, 2022.